"Wake up, remedy, tell ...": fortune tellers and doctors from the Andes / Mario Polia Meconi. Fondo Editorial de la Pontificia Universidad Católica, Lima, 1996 - Sánchez Benavides, Óscar (1997)
The review does not present a summary.